Super-fast-charging negative electrode sheet structure

CN117913208BActive Publication Date: 2026-10-16TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211248103.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-12
Publication Date
2026-10-16
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

但是依然存在石墨表面包覆层很难做到均匀一致,若存在未完全包覆区域,则存在析锂风险;其次是石墨与硅负极混合后涂布,由于石墨和硅在与锂反应时速率及机理不同,存在区域性分布不均,也易导致区域性析锂

Benefits of technology

[0018] (1) The arrangement of the above negative electrode structure can make the voltage plateau, lithium affinity, lithium intercalation capability and lithium plating risk layer form a gradient arrangement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117913208B_ABST
    Figure CN117913208B_ABST
Patent Text Reader

Abstract

The application discloses a kind of super fast charging negative pole piece structures, the structure includes in current collector at least one side to the outside sequentially coated graphite layer, carbon material layer and silicon-based material / lithiophilic metal composite layer.The arrangement of the negative pole piece structure of the application can form gradient arrangement of voltage platform, lithiophilic performance, lithium intercalation capacity, lithium risk layer;When battery is fast charged, lithium ion concentration gradient distribution from high to low is formed in the direction of electrolyte diffusion to current collector, so that the overall rate capability of negative pole piece is effectively improved;The capacity decay, thermal runaway and safety problem of battery caused by lithium dendrite generated by negative pole piece can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery anode material technology, specifically to a super-fast charging anode sheet structure. Background Technology

[0002] With the continuous development of the electric vehicle and consumer electronics markets, the development of corresponding fast-charging battery technology has become an important requirement. As the demand for charging speed increases, higher requirements are placed on the fast-charging performance of the negative electrode. During the charging of lithium-ion batteries, lithium migrates to the negative electrode. The high current of fast charging leads to a higher transition site, causing the negative electrode potential to become more negative. At this time, the pressure on the negative electrode to rapidly accept lithium increases, and the tendency to form lithium dendrites increases. Therefore, during fast charging, the negative electrode must not only meet the kinetic requirements of lithium diffusion, but also solve the capacity decay, thermal runaway, and safety issues caused by lithium dendrite formation.

[0003] Graphite is commonly used as the anode in lithium-ion batteries. However, the slow kinetics and lithium plating of traditional graphite anodes under fast-charging conditions hinder the rapid charging capability of lithium-ion batteries. Hard carbon materials are also used as anodes, but they suffer from low initial efficiency. Conventional hard carbon materials achieve only 70-80% coulombic efficiency during the first charge-discharge cycle, leading to significant irreversible capacity build-up during the initial charge and severely impacting the energy density improvement of lithium-ion batteries. Furthermore, the low compaction density of hard carbon materials is also detrimental to increasing the volumetric energy density of the battery. Silicon-based anodes have higher specific capacity than graphite anodes, but they also exhibit low initial charging efficiency. During the first charge of a lithium-ion battery, the organic electrolyte undergoes reduction and decomposition on the anode surface, forming a solid electrolyte interface film that irreversibly consumes a large amount of lithium ions from the cathode, resulting in a low coulombic efficiency during the first cycle. Current technologies improve the rate performance of the entire anode system by coating graphite materials with hard or soft carbon, or by doping the graphite system with hard carbon, soft carbon, or silicon-based anode materials. However, it is still difficult to achieve a uniform coating on the graphite surface. If there are incompletely coated areas, there is a risk of lithium plating. Secondly, when graphite is mixed with silicon anode and then coated, due to the different reaction rates and mechanisms of graphite and silicon with lithium, there is regional uneven distribution, which can also easily lead to regional lithium plating. Summary of the Invention

[0004] This invention addresses the problems in the prior art by disclosing a super-fast charging negative electrode structure, which can solve the battery capacity decay, thermal runaway and safety issues caused by lithium dendrites generated on the negative electrode during fast charging of lithium-ion batteries.

[0005] This invention is achieved through the following technical solution:

[0006] The present invention provides a super fast charging negative electrode structure, the structure comprising a graphite layer, a carbon material layer and a silicon-based material / lithophile metal composite layer sequentially coated outward from at least one side of the current collector.

[0007] The design of this invention features a gradually increasing lithium affinity, lithium insertion / extraction capability, and voltage platform (silicon-based material / lithophile metal layer ≥ carbon material layer > graphite layer). This creates a gradient reaction rate during fast charging, improving the overall lithium insertion capability of the negative electrode and enhancing rate performance. A larger voltage platform reduces the likelihood of lithium plating during insertion, mitigating the risk of lithium plating at the negative electrode interface during fast charging. Adding a lithiophile metal to the silicon-based material layer enhances its affinity for lithium, increasing the fast-charging lithium insertion reaction rate. Furthermore, when local defects or uneven charge distribution on the negative electrode lead to trace amounts of lithium plating, the metal adsorbs the generated elemental lithium, preventing lithium dendrite formation. This elemental lithium can then be extracted during delithiation, preventing dead lithium formation and capacity loss. The entire negative electrode structure exhibits a decreasing degree of order in the direction outward from the current collector. Compared to the ordered arrangement within the graphite layer, the carbon material layer exhibits a long-range disordered, short-range ordered structure. This long-range disordered structure generates numerous defects, thus providing a potential lithium deposit for lithium extraction. + Li provides numerous embedding sites, and due to the large interlayer spacing and randomly arranged crystal structure of carbon materials, Li + The diffusion coefficient in carbon materials is also significantly higher than that in graphite, resulting in better rate performance for the carbon material layer. This negative electrode structure, during fast charging, creates a gradient distribution of lithium-ion concentration from high to low along the diffusion direction from the electrolyte to the current collector, effectively improving the overall rate performance of the negative electrode.

[0008] As a further embodiment, the graphite material of the graphite layer includes one or more of artificial graphite, natural graphite, and composite graphite.

[0009] As a further embodiment, the carbon material of the carbon material layer includes one or more of hard carbon and soft carbon.

[0010] As a further option, the silicon-based material includes one or more of silicon suboxide, silicon carbon, nano-silicon, and silicon alloy.

[0011] As a further embodiment, the lithiophilic metal includes one or more of Ag, Mg, Sn, Ti, and metal-organic frameworks; as an even further embodiment, the lithiophilic metal is Ag; as an even further embodiment, the amount of Ag added is 1% of the total mass of the total active material, and the total mass of the total active material is the total mass of the graphite material in the graphite layer, the carbon material in the carbon material layer, and the silicon-based material.

[0012] As a further embodiment, the graphite layer has a thickness of 10-150 μm.

[0013] As a further embodiment, the thickness of the carbon material layer is 1-20 μm.

[0014] As a further embodiment, the thickness of the silicon-based material / lithophile metal composite layer is 1-100 μm.

[0015] As a further embodiment, the D50 of the graphite layer is 8-15 μm; the D50 of the carbon material layer is 5-10 μm; and the D50 of the silicon-based material in the silicon-based / lithophile metal composite layer is < 8 μm. As an even further embodiment, the D50 of the graphite layer is greater than the D50 of the carbon material layer, and the D50 of the carbon material layer is greater than the D50 of the silicon-based material in the silicon-based / lithophile metal composite layer. Since the entire negative electrode structure exhibits a decreasing orderliness trend in the direction outward from the current collector, changes in the number of defects will affect the Li... + Regarding the insertion / extraction efficiency, this invention, with its smaller particle distribution design and decreasing order, is more conducive to maintaining Li... + The insertion / extraction rate is balanced, promoting high-rate fast charging. Furthermore, as the D50 in each layer gradually increases, the conductivity gradually decreases from the current collector outwards, which is beneficial for the outward transport of electrons, thereby improving the electronic and ionic conductivity of the negative electrode and the overall reaction rate of the negative electrode with lithium.

[0016] As a further option, the current collector includes copper foil current collectors, PET / copper composite current collectors, Al foil current collectors, titanium foil current collectors, and Ag foil current collectors. It is not easily reduced at low voltages.

[0017] The features and beneficial effects of this invention are as follows:

[0018] (1) The arrangement of the above negative electrode structure can make the voltage plateau, lithium affinity, lithium intercalation capability and lithium plating risk layer form a gradient arrangement.

[0019] (2) When the battery is fast charged, a gradient distribution of lithium ion concentration from high to low can be formed in the direction of electrolyte diffusion to current collector, thereby effectively improving the overall rate performance of the negative electrode.

[0020] (3) It can solve the battery capacity decay, thermal runaway and safety problems caused by the formation of lithium dendrites on the negative electrode. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a schematic diagram of the negative electrode structure provided in an embodiment of the present invention.

[0023] Figure 2 This is a schematic diagram showing lithium plating occurring after fast charging of negative electrode sheets with different structures provided in the embodiments and comparative examples of the present invention.

[0024] The above figures include the following reference numerals:

[0025] 1-Current collector; 2-Graphite layer; 3-Carbon material layer; 4-Silicon-based material / lithophile metal composite layer. Detailed Implementation

[0026] To facilitate understanding of the structure of the super-fast charging negative electrode plate of the present invention, a more comprehensive description of the structure of the super-fast charging negative electrode plate of the present invention will be given below, and embodiments of the present invention will be provided, but this does not limit the scope of the present invention.

[0027] like Figure 1 As shown in the schematic diagram of the negative electrode structure provided in this embodiment of the invention, a graphite layer 2, a carbon material layer 3, and a silicon-based material / lithophile metal composite layer 4 are sequentially coated outwards on both sides of the current collector 1. The lithium affinity, lithium insertion / extraction capability, and voltage plateau of the negative electrode gradually increase (silicon-based material / lithophile metal layer 4 ≥ carbon material layer 3 > graphite layer 2), forming a gradient reaction rate during fast charging, which can improve the overall lithium insertion capability of the negative electrode and enhance rate performance. A larger voltage plateau makes lithium plating less likely during insertion, thus mitigating lithium plating at the electrode interface caused by fast charging and reducing safety risks. Adding a lithiophile metal to the silicon-based material can, on the one hand, improve lithium affinity and increase the fast-charging lithium insertion reaction rate; on the other hand, when local defects or uneven charge distribution in the negative electrode lead to trace amounts of lithium plating, it can adsorb the generated elemental lithium, preventing lithium dendrite formation. Simultaneously, this elemental lithium can continue to be extracted during delithiation at the negative electrode, preventing dead lithium formation and avoiding capacity loss. The entire negative electrode structure exhibits a decreasing degree of order in the direction outward from the current collector. Compared to the ordered arrangement within graphite layer 2, carbon material layer 3 exhibits a long-range disordered, short-range ordered structure. This long-range disordered structure generates numerous defects, thus providing a potential source of Li... + It provides numerous embedding sites, and due to the large interlayer spacing and randomly arranged crystal structure of the carbon material layer 3, Li + The diffusion coefficient in carbon material layer 3 is also significantly higher than that in graphite layer 2, giving carbon material layer 3 better rate performance. The above-mentioned negative electrode structure can form a gradient distribution of lithium ion concentration from high to low in the diffusion direction of the electrolyte to the current collector 1 during fast charging, thereby effectively improving the overall rate performance of the negative electrode.

[0028] To further investigate the lithium plating of negative electrode sheets with different structures and the battery capacity retention during fast charging, we also provide examples and comparative examples.

[0029] In this invention, each layer of the negative electrode sheet is prepared by coating. Each layer is coated onto the current collector after being uniformly mixed with an active material and a binder. The lithium-loving metal is selected from Ag, and the amount of Ag added is 1% of the total mass of the total active material.

[0030] Example 1: The negative electrode uses the above three-layer coating, from the inside out: First layer: graphite layer, made of artificial graphite, with a specific capacity of 350mAh / g, a D50 of 13μm, and an areal density of 136g / m³. 2 The second layer is a carbon material layer, made of hard carbon with a specific capacity of 300 mAh / g, a D50 of 9 μm, and an areal density of 8 g / m³. 2 The third layer is a hybrid layer of silicon-based material and lithium-loving metal, wherein the silicon-based material is silicon suboxide with a specific capacity of 1600 mAh / g, a D50 of 6 μm, and an areal density of 16 g / m³. 2 The lithium-loving metal is Ag, added at 1% of the total active material, with a particle size of 100 nm.

[0031] Example 2: The negative electrode adopts the above three-layer coating, from the inside out as follows: First layer: graphite layer, using artificial graphite, with a specific capacity of 350mAh / g, D50 of 13μm, and areal density of 136g / m³. 2 The second layer is a carbon material layer, using soft carbon with a specific capacity of 300 mAh / g, a D50 of 8 μm, and an areal density of 8 g / m³. 2 The third layer is a hybrid layer of silicon-based material and lithium-loving metal, wherein the silicon-based material is silicon suboxide with a specific capacity of 1600 mAh / g, a D50 of 6 μm, and an areal density of 16 g / m³. 2 The lithium-loving metal is Ag, added at 1% of the total active material, with a particle size of 100 nm.

[0032] Example 3: The negative electrode uses the above three-layer coating, from the inside out: First layer: graphite layer, made of artificial graphite, with a specific capacity of 350 mAh / g, a D50 of 13 μm, and an areal density of 136 g / m³. 2 The second layer is a carbon material layer, made of hard carbon with a specific capacity of 300 mAh / g, a D50 of 9 μm, and an areal density of 8 g / m³. 2 The third layer is a hybrid layer of silicon-based material and lithium-loving metal, wherein the silicon-based material is silicon-carbon with a specific capacity of 1400 mAh / g, a D50 of 7 μm, and an areal density of 18.286 g / m³. 2 The lithium-loving metal is Ag, added at 1% of the total active material, with a particle size of 100 nm.

[0033] Comparative Example 1: The negative electrode uses a single-layer coating, with an electrode surface density of 160 g / m². 2 The active material comprises 85% artificial graphite, 5% hard carbon, and 10% silicon suboxide. Ag is added at 1% of the total active material.

[0034] Comparative Example 2: The negative electrode uses a three-layer coating, from the inside out: First layer: Silicon-based material / lithophile metal hybrid layer, wherein the silicon-based material is silicon suboxide, with a specific capacity of 1600 mAh / g, a D50 of 6 μm, and an areal density of 16 g / m³. 2 The lithiophilic metal is Ag, added at 1% of the total active material, with a particle size of 100 nm. The second layer is a carbon material layer, using hard carbon with a specific capacity of 300 mAh / g, a D50 of 9 μm, and an areal density of 8 g / m³. 2 The third layer is a synthetic graphite layer with a specific capacity of 350 mAh / g, a D50 of 13 μm, and an areal density of 136 g / m³. 2 .

[0035] Comparative Example 3 uses a double-layer coating for the negative electrode, from the inside out: First layer: graphite layer, with an areal density of 136 g / m³. 2 The density of the second layer is 24 g / m³. 2 The second layer is a mixed layer of carbon material / silicon-based material / lithophile metal. Hard carbon accounts for 33.33% of the active material, and silicon suboxide accounts for 66.67%. The lithiophile metal is Ag, which is added at 1% of the total active material and has a particle size of 100 nm.

[0036] Comparative Example 4: The negative electrode uses a double-layer coating, from the inside out: the first layer is a mixed layer of graphite and carbon materials with an areal density of 144 g / m³. 2 The first layer of active material contains 94.44% graphite and 5.56% hard carbon; the second layer is a mixture of silicon suboxide and lithium-loving metal with an areal density of 16 g / m³. 2 The lithium-loving metal is Ag, added at 1% of the total active material, with a particle size of 100 nm.

[0037] Comparative Example 5: The negative electrode uses a three-layer coating, from the inside out: First layer: graphite layer, made of artificial graphite, with a specific capacity of 350 mAh / g, a D50 of 13 μm, and an areal density of 136 g / m³. 2 The second layer is a carbon material layer, made of hard carbon with a specific capacity of 300 mAh / g, a D50 of 9 μm, and an areal density of 8 g / m³. 2 The third layer is a silicon-based material layer, wherein the silicon-based material is silicon suboxide, with a specific capacity of 1600 mAh / g, a D50 of 6 μm, and an areal density of 16 g / m³. 2 .

[0038] Comparative Example 6: The negative electrode uses a four-layer coating, from the inside out: First layer: artificial graphite layer, surface density 136 g / m³ 2 The first layer has a D50 of 13 μm; the second layer is a hard carbon layer with a surface density of 8 g / m³. 2 D50 is 9μm; the third layer is a silicon suboxide layer with an areal density of 16g / m³. 2 The D50 is 6μm. The fourth layer is an Ag powder layer, added at 1% of the total active material.

[0039] Comparative Example 7: The negative electrode uses a three-layer coating, from the inside out: First layer: Silicon-based material / lithophile metal hybrid layer, wherein the silicon-based material is silicon suboxide, with a specific capacity of 1600 mAh / g, a D50 of 6 μm, and an areal density of 16 g / m³. 2 The second layer is a graphite layer made of artificial graphite with a specific capacity of 350 mAh / g, a D50 of 13 μm, and an areal density of 136 g / m³. 2 The third layer is a carbon material layer, made of hard carbon with a specific capacity of 300 mAh / g, a D50 of 9 μm, and an areal density of 8 g / m³. 2 The amount of Ag added is 1% of the total active substances.

[0040] Comparative Example 8: The negative electrode uses a three-layer coating, from the inside out: First layer: graphite layer, made of artificial graphite, with a specific capacity of 350 mAh / g, a D50 of 13 μm, and an areal density of 136 g / m³. 2 The second layer is a hybrid layer of silicon-based material and lithium-loving metal, wherein the silicon-based material is silicon suboxide with a specific capacity of 1600 mAh / g, a D50 of 6 μm, and an areal density of 16 g / m³. 2 The third layer is a carbon material layer, made of hard carbon with a specific capacity of 300 mAh / g, a D50 of 9 μm, and an areal density of 8 g / m³. 2 The amount of Ag added is 1% of the total active substances.

[0041] Comparative Example 9: The negative electrode uses a three-layer coating, from the inside out: First layer: carbon material layer, using hard carbon with a specific capacity of 300 mAh / g, a D50 of 9 μm, and an areal density of 8 g / m³. 2 The second layer is a graphite layer made of artificial graphite with a specific capacity of 350 mAh / g, a D50 of 13 μm, and an areal density of 136 g / m³. 2 The third layer is a hybrid layer of silicon-based material and lithium-loving metal, wherein the silicon-based material is silicon suboxide with a specific capacity of 1600 mAh / g, a D50 of 6 μm, and an areal density of 16 g / m³. 2 The amount of Ag added is 1% of the total active substances.

[0042] Comparative Example 10: The negative electrode uses a three-layer coating, from the inside out: First layer: carbon material layer, using hard carbon with a specific capacity of 300 mAh / g, a D50 of 9 μm, and an areal density of 8 g / m³. 2 The second layer is a hybrid layer of silicon-based material and lithium-loving metal, wherein the silicon-based material is silicon suboxide with a specific capacity of 1600 mAh / g, a D50 of 6 μm, and an areal density of 16 g / m³. 2 The third layer is a graphite layer made of artificial graphite with a specific capacity of 350 mAh / g, a D50 of 13 μm, and an areal density of 136 g / m³. 2 The amount of Ag added is 1% of the total active substances.

[0043] The electrode sheets prepared above are matched with LCO positive electrodes, and the processes of stacking, packaging, liquid injection, and formation are completed. The prepared battery cells are tested under low-rate charge and discharge conditions and 50 cycles of fast charging at room temperature.

[0044] The specific test conditions for low-rate charge and discharge test are as follows: (1) let stand for 10 minutes; (2) discharge at 0.1C to 3V; (3) let stand for 10 minutes; (4) charge at 0.1C to 4.48V and keep the voltage constant at 0.025C; (5) repeat the above steps twice.

[0045] The fast charging cycle test was conducted 50 times under the following conditions: (1) rest for 10 minutes; (2) discharge at 1.5C to 3V; (3) rest for 10 minutes; (4) charge at 7C to 4.2V and maintain the voltage at 5C; (5) charge at 5C to 4.3V and maintain the voltage at 4C; (6) charge at 4C to 4.4V and maintain the voltage at 3C; (7) charge at 3C to 4.48V and maintain the voltage at 0.025C; (8) repeat the above steps 50 times.

[0046] We categorized lithium plating into 10 levels based on severity, with higher values ​​indicating more severe plating. The overall characteristics of the 10 levels are shown in Table 1.

[0047] Table 110 Lithium Plating Status by Grade

[0048]

[0049]

[0050] Table 2. Structures of negative electrode sheets with different structures

[0051]

[0052] Table 3 Cell Test Data

[0053]

[0054] As shown in Table 2, we selected three representative negative electrode sheets as Examples 1-3, and ten different negative electrode sheets as Comparative Examples 1-10. Examples 1-3 are the negative electrode sheet structures of the present invention, in which a graphite layer, a carbon material layer, and a silicon-based material / lithophile metal composite layer are arranged sequentially on both sides of the current collector (e.g., ...). Figure 1 As shown in the figure), and meeting the condition that the D50 of the graphite layer > the D50 of the carbon material layer > the D50 of the silicon-based material / lithophile metal composite layer, the conductivity gradually increases from the graphite layer to the silicon-based material / lithophile metal composite layer, which is beneficial for electrolyte wetting and electron transport to the outer coating, improving the electronic and ionic conductivity of the electrode, thereby improving the overall reaction rate of the negative electrode with lithium. In contrast, in Comparative Examples 1-10, the order and method of coating on the current collector are different, and the D50 of each coating layer is not limited. We conducted low-rate charge-discharge tests and 50-cycle fast charging tests on Examples 1-3 and Comparative Examples 1-10, and the results are shown in Table 3. From Table 3, we can see that in Examples 1-3, no lithium plating occurred on the negative electrode after 50 cycles, while Comparative Examples 1-5 and Comparative Examples 7-10 all showed varying degrees of lithium plating (e.g., ...). Figure 2 As shown in the figure, the structure of the negative electrode sheet of the present invention can solve the problem of lithium dendrite formation during fast charging. Although Comparative Example 6 also showed no lithium plating and had good capacity retention and 0.1C discharge capacity, the metal layer on the surface of the negative electrode sheet poses a safety risk when the cell self-discharge is large.

[0055] We further investigated the effect of different coating sequences on the battery capacity retention. Compared to Examples 1-3, Comparative Examples 2, 5, and 7-10 all exhibited lower capacity retention after 50 cycles, with Comparative Example 2 showing the lowest retention. We believe that coating in the order of increasing lithiophilicity, lithium insertion / extraction capability, and voltage plateau (silicon-based material / lithophile metal layer ≥ carbon material layer > graphite layer) can create a gradient reaction rate during fast charging, improving the overall lithium insertion capability of the electrode and enhancing rate performance. Adding a lithiophilic metal to the silicon-based material layer can improve lithium affinity and increase the fast-charging lithium insertion reaction rate. Furthermore, when local defects and uneven charge distribution in the negative electrode lead to trace lithium deposition, the metal can adsorb the generated elemental lithium, preventing lithium dendrite formation. This elemental lithium can also be extracted during negative electrode delithiation, preventing dead lithium formation and thus avoiding capacity loss.

[0056] We further investigated the effect of different coating methods on the current collector on the battery's 0.1C discharge capacity. Compared to Examples 1-3, Comparative Examples 1 and 3-4 showed lower 0.1C discharge capacities, with Comparative Example 1 exhibiting the lowest capacity. We believe that the internal structure of the negative electrode plate shows a decreasing trend in orderliness in the direction outward from the current collector. Compared to the ordered arrangement within the graphite layer, the carbon material layer exhibits a highly disordered internal structure. This disordered structure generates numerous defects, thus providing a potential advantage for Li... + Li provides numerous embedding sites, and due to the large interlayer spacing and randomly arranged crystal structure of the carbon material layers, Li... + The diffusion coefficient in the carbon material layer is significantly higher than that in the graphite layer, giving the carbon material layer better rate performance. This trend of decreasing internal order in the negative electrode structure can create a gradient distribution of lithium-ion concentration from high to low in the direction from the electrolyte to the current collector during fast charging, thereby effectively improving the overall rate performance of the negative electrode. Furthermore, with the decrease in order, coupled with a smaller particle distribution design (D50 of graphite layer > D50 of carbon material layer > D50 of silicon-based material / lithophile metal composite layer), it is beneficial to maintain the Li + The insertion and extraction rates are balanced, thus promoting high-rate fast charging. However, mixing the coating layers to form a hybrid coating layer will break this combination advantage, thereby reducing the rate performance of the negative electrode.

[0057] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A super-fast charging negative electrode structure, characterized in that, The structure comprises a graphite layer, a carbon material layer, and a silicon-based material / lithophile metal composite layer sequentially coated outward from at least one side of the current collector; or, the structure comprises a graphite layer, a carbon material layer, and a silicon-based material / metal-organic framework composite layer sequentially coated outward from at least one side of the current collector.

2. The super-fast charging negative electrode structure according to claim 1, characterized in that, The graphite material of the graphite layer includes one or more of artificial graphite, natural graphite, and composite graphite.

3. The super-fast charging negative electrode structure according to claim 1, characterized in that, The carbon material in the carbon material layer includes one or more of hard carbon and soft carbon.

4. The super-fast charging negative electrode structure according to claim 1, characterized in that, The silicon-based material includes one or more of silicon suboxide, silicon carbon, nano-silicon, and silicon alloy.

5. The super-fast charging negative electrode structure according to claim 1, characterized in that, The lithiophilic metal includes one or more of Ag, Mg, Sn, and Ti.

6. The super-fast charging negative electrode structure according to claim 5, characterized in that, The lithium-loving metal is Ag.

7. The super-fast charging negative electrode structure according to claim 6, characterized in that, The amount of Ag added is 1% of the total mass of the total active material, which is the total mass of the graphite material in the graphite layer, the carbon material in the carbon material layer, and the silicon-based material.

8. The super-fast charging negative electrode structure according to claim 1, characterized in that, The graphite layer has a thickness of 10-150 μm, the carbon material layer has a thickness of 1-20 μm, and the silicon-based material / lithophile metal composite layer has a thickness of 1-100 μm.

9. The super-fast charging negative electrode structure according to claim 1, characterized in that, The graphite material in the graphite layer has a D50 of 8-15 μm, the carbon material in the carbon material layer has a D50 of 5-10 μm, and the silicon material in the silicon-based material / lithophile metal composite layer has a D50 of <8 μm.

10. The super-fast charging negative electrode structure according to claim 1, characterized in that, The D50 of the graphite material in the graphite layer is greater than that of the carbon material in the carbon material layer, and the D50 of the carbon material in the carbon material layer is greater than that of the silicon-based material / lithophile metal composite layer.

11. The super-fast charging negative electrode structure according to claim 1, characterized in that, The current collectors include copper foil current collectors, PET / copper composite current collectors, Al foil current collectors, titanium foil current collectors, and Ag foil current collectors.

Citation Information

Patent Citations

  • Quick-charging negative plate

    CN218887229U